2021
DOI: 10.51847/cj6189cibl
|View full text |Cite
|
Sign up to set email alerts
|

The effect of brain GYM on the dementia and depression reduction of the elderly‎

Abstract: This study aims to determine the effect of brain gym on decreasing the level of dementia and depression in the elderly in the Health Center Community of Mulyorejo in Deli Serdang Regency. The population of this study was 5765 elderly people. The sampling technique uses the Slovin formula and it is determined through inclusion criteria using a purposive consecutive method so that the total sample of 30 respondents is divided into two groups, 15 respondents with dementia and 15 respondents with depression. A qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Additionally, these interventions have been associated with a reduction in stress, anxiety levels and quality of life among the elderly population [50][51][52]. Moreover, they have been linked to a decrease in the incidence of dementia and depression in older adults [29]. Lastly, brain gym exercises have been found to have positive effects on cognitive function, functional independence, quality of life, and fitness levels in older individuals with cognitive impairment [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these interventions have been associated with a reduction in stress, anxiety levels and quality of life among the elderly population [50][51][52]. Moreover, they have been linked to a decrease in the incidence of dementia and depression in older adults [29]. Lastly, brain gym exercises have been found to have positive effects on cognitive function, functional independence, quality of life, and fitness levels in older individuals with cognitive impairment [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Brain gym, conversely, is a therapeutic intervention that has the potential to augment the immune response in individuals with chronic conditions, such as HIV/AIDS. Research has demonstrated that persons with chronic conditions see a decrease in depression levels, resulting in an overall enhancement in their quality of life [29]. By incorporating PSCM and brain gym techniques into the provision of healthcare for PLHIV, there exists a potential avenue for enhancing ART adherence, and eventually augmenting the overall quality of life experienced by these persons.…”
Section: Introductionmentioning
confidence: 99%
“…Згідно з іншими дослідженнями вправи Brain Gym покращують рівновагу у пацієнтів з нейропатіями, що дає надію на покращення неврологічних станів . Окрім цього, були встановлені позитивні ефекти після застосування нейрогімнастики в різних групах населення для лікування проблем психічного здоров'я та покращення якості життя (Andi P. et al, 2019;Surita G. et al, 2021).…”
Section: The Neurogymnastics As An Effective Methods Of Improving The...unclassified
“…According to Anggraini and Dewi (2022), concentration increases significantly, improving the teaching and learning process with the use of Brain Gym. At the level of academic performance of university students, according to Ramírez et al (2021), the influence of Brain Gym exercises applied as a didactic strategy in Physical Education, reported (Surita et al, 2021).…”
Section: Introductionmentioning
confidence: 99%